Estimation problem of electromagnetic fields influence on ergatic systems characteristics reliability - Іванов, В. О.; Ільницький, Л. Я.; Петрашевський, O. Л.; Богатир, В. Т. (Proceedings of National Aviation University (archive), 1998)
Substantiated is the hypothesis about influence of low power non-ionizing electromagnetic field on quantity of mistake which are permited in the process of taking decision as to complex control system. On scheme structural levee given is the continuous property dependence (no-failure) of system maintenance and its completeness (improved information reliability), on human operator possible state. The concept of biological electromagnetic compatibility of man-operator which is considered to be a special subsystem of ergatic system of urgent responsibility is worked out